Translation of hardware description languages to structured representation: a tool for digital system analysis - Peixoto, Daniela C.; Silva Jr., Diógenes; Mata, José M.; Coelho Jr., Claudionor N.; Fernandes, Antônio O. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance Computing, 2001)
SDS (System Data Structure), part of a digital synthesis system, is an internal representation that captures data/operation and communication/synchronization aspects from the behavioral specification of a digital system. SDS divides design information into two graphs that describe the data flow behavior and control timing behavior. This representation is useful for synthesis and validation/verification. This paper presents the translation process from the hardware description language VHDL to SDS, basically the transformation of a behavioral specification to a structured representation.